2000
DOI: 10.1086/315870
|View full text |Cite
|
Sign up to set email alerts
|

Prevention ofHaemophilus influenzaeType b Colonization by Vaccination: Correlation with Serum Anti‐Capsular IgG Concentration

Abstract: Concentrations of serum anti-Haemophilus influenzae type b (anti-Hib) capsular polysaccharide (CPS) >/=0.15 and >/=1.0 microgram/mL are widely used as surrogates for protection against invasive Hib disease. However, the relationship between serum anti-Hib CPS following immunization and protection against colonization is not known, making it difficult to evaluate new Hib vaccines or combination vaccines. In the Dominican Republic, nasopharyngeal swabs were collected from 546 9-month-old infants who had received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 12 publications
2
53
0
1
Order By: Relevance
“…24 Hib colonizes naso and oro pharyngeal mucosa review review >5.0 μg/ml were significantly less likely to be colonized with Hib at nine months of age. 23,57 The impact of herd immunity is said to reduce invasive disease rates by ten times in unvaccinated children under the age of one year compared with pre-vaccination risk. 56,57 A resurgence of Hib disease among Alaskan children in the 1990s, lead authors to suggest that special attention is required to eliminate Hib disease and carriage in high-risk populations.…”
Section: Hib Carriage Immune-epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…24 Hib colonizes naso and oro pharyngeal mucosa review review >5.0 μg/ml were significantly less likely to be colonized with Hib at nine months of age. 23,57 The impact of herd immunity is said to reduce invasive disease rates by ten times in unvaccinated children under the age of one year compared with pre-vaccination risk. 56,57 A resurgence of Hib disease among Alaskan children in the 1990s, lead authors to suggest that special attention is required to eliminate Hib disease and carriage in high-risk populations.…”
Section: Hib Carriage Immune-epidemiologymentioning
confidence: 99%
“…25 However, despite the marked disappearance of invasive Hib disease, some studies encompassing mostly Indigenous populations report persisting Hib carriage, albeit at lower levels than pre-vaccination carriage. 2,11,21,23,50,53 The issue of persistent Hib carriage in vaccinated populations occurs globally, mostly in minority populations, often despite high levels of vaccine uptake. 2,12 A study of Native Alaskans reported Hib oropharyngeal carriage as high as 9.3% in fully vaccinated under five year old children.…”
Section: Risks Associated With Hib Carriagementioning
confidence: 99%
See 3 more Smart Citations